E-learning in Epidemic periods in the Colleges of Education in Sudan (Corona Epidemic as a Sample) - Balla, Elsiddig Abdelsadig Elbadawi (Social Empowerment Journal, 2021)
The study aimed to identify the necessity of e-learning, and the extent of the existence of e-learning obstacles among students, and the degree of availability of e-learning competencies among teaching staff, and the degree of availability of e-learning requirements in the colleges, as well as, identifying statistically significant differences among the examinees with regards to the possibility of employing e-learning in the colleges of education, which are due to two variables: type and job grade. The study used the descriptive method with a population consisted of university lecturers at the colleges of education in Sudan. The study was conducted through the academic year 2019/2020. To achieve the objectives of the study, the questionnaire was used as a tool after verifying its validity and reliability, and it was designed, filled and analyzed electronically. A random sample was chosen consisted of (228) teachers. For processing the data statistically, the Statistical Package for Social Sciences (SPSS) program was used. The study reached several results: The necessity of e-learning in epidemics period is achieved by an arithmetic mean reaching 2.36 and with a high degree of appreciation, and there are evident obstacles to e-learning among students with an arithmetic mean of 2.44 with a high degree of appreciation, and the existence of e-learning competencies among the teaching staff is achieved by an arithmetic mean around 2.22 with average grade, and the availability of e-learning requirements in the Sudanese colleges of education is achieved with an arithmetic mean of 1.85 and with an average grade, and there are no statistically significant differences among the respondents in the extent of employing e-learning in colleges of education due to the type, and there are statistically significant differences in favor of the higher academic degree (professor).